Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry Can Accurately Differentiate between Mycobacterium masilliense (M. abscessus subspecies bolletti) and M. abscessus (Sensu Stricto) - Teng, Shih-Hua (American Society for Microbiology, 2013)
Among 36 Mycobacterium masilliense and 22 M. abscessus isolates identified by erm(41) PCR and sequencing analysis of rpoB and 23S rRNA genes, the rate of accurate differentiation between these two subspecies was 100% by cluster analysis of spectra generated by Bruker Biotyper matrix-assisted laser desorption ionization–time of flight mass spectrometry.